2015
DOI: 10.1016/j.ijge.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of Long-term Care Facility Employees: Relationship with Employees' Expressed Emotion Toward Patients

Abstract: Abstract:Background: This study determined factors related to the burnout of long-term care facility employees, including employees' expressed emotion (EE) toward patients.Methods: A survey of 411 long-term care facility employees was conducted. Employee burnout was evaluated with the Maslach Burnout Inventory (MBI). EE levels were evaluated using the Nurse Attitude Scale (NAS). Conclusion: Results indicate that employees' EE of criticism and hostility toward patients is related to burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…In LTC settings, the high prevalence of burnout among nurses [ 3 , 17 , 45 , 46 ] and its repercussions on care quality [ 46 , 47 ] have been documented. For instance, higher burnout was associated with lower residential satisfaction [ 15 ], lower perceived quality-of-life [ 15 ], more depressive symptoms among residents [ 15 ], expressed emotions of criticism and hostility toward patients [ 48 ], and inadequate provision of comfort and support care [ 49 ]. Previous research also documented significant associations between hospital nurses’ burnout and negative patient outcomes, such as falls [ 20 , 21 ] and nosocomial infection [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In LTC settings, the high prevalence of burnout among nurses [ 3 , 17 , 45 , 46 ] and its repercussions on care quality [ 46 , 47 ] have been documented. For instance, higher burnout was associated with lower residential satisfaction [ 15 ], lower perceived quality-of-life [ 15 ], more depressive symptoms among residents [ 15 ], expressed emotions of criticism and hostility toward patients [ 48 ], and inadequate provision of comfort and support care [ 49 ]. Previous research also documented significant associations between hospital nurses’ burnout and negative patient outcomes, such as falls [ 20 , 21 ] and nosocomial infection [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We only examined burnout and stress in long-term care settings and it would be unsurprising if this varied between settings. For example, two studies in Japan in intermediate care and psychiatric hospitals reported high levels of burnout and stress in care staff (Tanaka et al 2015,Yada et al 2014). This may be because of higher care needs and more challenging behavioural symptoms of patients which are associated with burnout level of staff (Agoub, Elyazaji et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Cooper et al [10] showed that individual demographic factors such as being married, older, more educated, and having a sense of optimism had a buffering effect on burnout. In Japan, Tanaka et al [11] reported that burnout was related to feelings of criticism and hostility towards residents among long-term care facility employees. To the best of our knowledge, however, relationships between burnout, provision of end-of-life care and religion in long-term care facilities have not been discussed.…”
Section: Introductionmentioning
confidence: 99%